A Strategy for the Management of Education and Sports Achievement in the Completion of Studies for Students at PJKR FKIP USK - Isdarianti, Novi Lidya; Fajrial, Jul; Azmi, Fahrul; Syukriadi, Amanda; Ridha, Fahlul; Mansur, Mansur (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. Education is crucial for cultivating humanity and realizing individuals' greatest potential. Education enables individuals to understand their rights and obligations, while also allowing them to contribute to society and honor God. Physical education and sports constitute a fundamental component of education, designed to enhance persons' quality of life, both physically and spiritually. This study seeks to analyze the technique for managing educational and athletic accomplishments in the academic pursuits of PJKR FKIP USK pupils. This study was prompted by the challenges encountered by PJKR FKIP USK students in balancing their time between lectures and training, together with the insufficient support from lecturers for training permissions. These impediments adversely affect academic and athletic performance. Consequently, a robust management plan is essential to facilitate timely completion of studies and attainment of athletic accomplishments for pupils. This research is a qualitative descriptive analysis. Materials and Methods. The research methodology encompassed observation and interviews with faculty and students at PJKR FKIP USK. Results. The analysis indicated that the primary hurdles were scheduling conflicts between lectures and practical sessions, inadequate time management, and insufficient support from certain professors for practice permissions. Conclusion. The proposed method entails dialogue and consensus between lecturers and students to modify schedules, along with enhanced time management strategies.